Preliminary studies into the effect of environmental degradation on the characterisation of automotive clear coats by attenuated total reflectance infrared spectroscopy - Sauzier, Georgina; Maric, Marc; Van Bronswijk, Wilhelm; Lewis, Simon (R S C Publications, 2013)
This paper presents a study into the impact of environmental weathering on the chemometric classification of automotive clear coats. These studies were conducted using attenuated total reflectance infrared spectroscopy, in conjunction with a chemometric model capable of predicting the country of vehicle manufacture for a sample based upon its infrared spectrum. Testing of three samples exposed to environmental conditions found the model to be robust to weathering over at least an eight-month period. However, analysis of 12 samples of unknown prior history found that extreme degradation over at least a 10-year period, or the presence of a post-manufacture (respray) coating, could result in misclassification when relying solely on analysis of the clear coat. It is therefore important that cross-sections comprising the full layer sequence of the paint system are obtained wherever possible, as analysis of the underlying layers may give more comprehensive characterisation.